Constructive alignment and authentic assessment in a media-rich undergraduate course. Issue 2 (2nd April 2020) - Nurmikko-Fuller, Terhi; Hart, Ian E
ABSTRACT: This paper describes the process of constructive alignment of the content and assessment of a first year university course on Digital Culture. Previous iterations of the course assessed the students using only written assignments, which proved to be problematic. In 2019 the course team decided to revise the assessment tasks in order to align them more closely with the media that the students were studying. We describe our methodology for constructive alignment that begins with a close examination of the learning outcomes (LOs), considers the authentic activities that support these LOs and develops assessment tasks, which are authentic and valid. We also describe how group projects contributed to the course structure and how peer assessment was designed to provide formative feedback to the students.